2016
DOI: 10.1016/j.psyneuen.2016.07.204
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing hormone receptor 1 (CRH-R1) polymorphisms are associated with irritable bowel syndrome and acoustic startle response

Abstract: BACKGROUND Corticotropin-releasing hormone receptor 1 (CRH-R1) in the amygdala and the stria terminalis plays an important role in the activation of central stress circuits. Genetic factors may contribute to the hyperresponsiveness of these circuits in irritable bowel syndrome (IBS). AIMS To determine if CRH-R1 SNPs are associated with: 1) a diagnosis of IBS, 2) gastrointestinal (GI) symptoms, and 3) acoustic startle response (ASR) to threat, which is mediated by the amygdala via CRH. METHODS Three CRH-R1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Another meta-analysis showed a decreased risk of IBS in subjects with the l/s gene and increased risk of IBS-C in those with the s/s gene as well as populational differences between Asian and EU/US cohorts [ 53 ]. Some associations between IBS and CRH-related genes (CRH, CRH binding protein [ 54 ], CRH-R1 [ 55 ], and CRH-R2 [ 56 ]) were identified and replicated [ 57 ].…”
Section: Main Text Of the Japanese Ibs Guidelinesmentioning
confidence: 99%
“…Another meta-analysis showed a decreased risk of IBS in subjects with the l/s gene and increased risk of IBS-C in those with the s/s gene as well as populational differences between Asian and EU/US cohorts [ 53 ]. Some associations between IBS and CRH-related genes (CRH, CRH binding protein [ 54 ], CRH-R1 [ 55 ], and CRH-R2 [ 56 ]) were identified and replicated [ 57 ].…”
Section: Main Text Of the Japanese Ibs Guidelinesmentioning
confidence: 99%
“…CRH increases in the serum of patients with IBS and can cause diarrhea by increasing intestinal movements through its receptor (CRHR1) in response to anxiety [8, 9]. In addition, peripheral inflammation stimulates the release of CRH by upregulation of ACTH production, which is an indication of IBS symptoms [38].…”
Section: Discussionmentioning
confidence: 99%
“…CRHR2 has a completely opposite function compared to CRHR1 [11]. CRHR1 is mostly found in the myenteric plexus, and prescription of a CRHR1 antagonist in IBS patients can suppress colonic movements and abdominal pain [9]. Low-grade inflammation is observed in the intestinal epithelium of patients with IBS [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the major alleles of CRHR1 rs110402, rs242924 and rs720943 (all C) were associated with increased risk for IBS and, within IBS patients, increased GI-symptom-related anxiety. Unexpectedly, IBS patients with the same risk alleles showed reduced acoustic startle responses vs. healthy controls, whereas those with the minor alleles did not, indicating a complex influence of the CRHR1 SNPs on different symptoms of anxiety per diagnostic group (Orand et al 2016). Finally, a separate study of young Japanese individuals observed that the CRHR1 rs10474485 locus was associated with increased psychometric scores for depression, perceived stress or state/trait anxiety in IBS patients with diarrhea or mixed symptoms, with the CRHR1 variant more predictive of differences in emotional scales in women than in men (Sasaki et al 2016).…”
Section: Recent Genetic and Molecular Findings In Humansmentioning
confidence: 99%